The truly brave princesses - Brown, Dolores (Children's author) (Egalité series., 2018)
"Princess Nin is a firefighter, Princess Gilda is a supermarket cashier, Princess Agnes is retired, and Princess Liang is in a wheel chair. This gallery of princesses gives visibility to lot of women who do not fit with the traditional conception of a princess. Maybe it's time to realize that each and every one of us could be a princess"--Amazon.com.